Geomechanics and geodynamics of rock masses. Volumes 1 and 2 : proceedings of the 2018 European Rock Mechanics Symposium (Eurock 2018), Saint Petersburg, Russia, 22-26 May 2018 - Litvinenko, Vladimir (CRC Press, 2018)
Geomechanics and Geodynamics of Rock Masses contains the contributions presented at EUROCK 2018, the 2018 Interanational Symposium of the International Society for Rock Mechanics (ISRM 2018, Saint Petersburg, Russia, 22-26 May 2018).